Storytelling Method to Improve Vocabulary for Non-Native Arabic Speaker Children - Akla, Akla (Institut Agama Islam Negeri Curup, 2022)
The purpose of this study is to investigate; (1) the method of using storytelling to learn Arabic vocabulary, (2) the emotional state of students when using storytelling to learn, and (3) the impact of storytelling on boosting students' Arabic vocabulary. This study uses Mixed Method Research. Students from the al-Imam Islamic boarding school Metro Kibang East Lampung, a total of 40 students, participated in the study. Observation and testing are the methods used to obtain data. The method of observation was employed to obtain data on the process of using storytelling to acquire the Arabic language vocabulary. The test was conducted to collect information regarding the level of knowledge of Arabic vocabulary before and after using the storytelling. Data was analyzed in two ways. First, qualitative analysis. Second, quantitative analysis was carried out with prerequisite tests and t-tests. The study's findings show that (1) the use of storytelling to learn Arabic stimulates teachers' creativity in developing interesting learning strategies, makes Arabic learning easier, and increases positive emotions, (2) the use of storytelling to learn Arabic has increased children's positive emotions in learning, such as creating enthusiastic and happy behavior in following a series of learning processes, and (3) the use of storytelling to learn Arabic has a significant effect on mastery of Arabic vocabulary. Learning Arabic is easier with the use of storytelling in the form of intriguing and enjoyable stories that are relevant to children's development.